Kinetic Waves - Dynamics of Light Propagation - Rota, Luciano M.R. (JOURNAL OF ADVANCES IN PHYSICS, 2018)
An in-depth analysis of the dynamics connected to the Doppler-effect brings clear light to elements of contradiction with the original ground on which the axiom of the constancy of lightspeed was based. Thereby, with regard to electromagnetic phenomenology, the duality waves/particles and the wavy dynamic of light-propagation suggest the existence of a natural kind of waves, which differently from the classic ones, are originating by kinetic thrust and propagating, also though vacuum, by inertial force. The model taken into consideration, to which has been given the name of kinetic waves is, like the classic one, a concretely existing natural phenomenon which can also be visually perceived if produced on molecular scale. Moreover kinetic waves seem to offer many more points of similarity, in dynamic and behavior, with the electromagnetic waves, than the classic model. Applying the obtained results on the astrophysical field, taking as example the quasar 3C-273, the recently found, most far galaxy GN-z11 and the galaxy NGC 224 (better known as Andromeda), can mathematically and concretely be sustained that none of the energy sources we optically perceive, showing a Doppler-shift, nor is approaching nor regressing. In the appendix, a suggested and accurately described experiment on base of Radar Astronomy to possibly confirm the validity of the model presented by this article.